Community-Centered Farm-Based Hospitality in Agriculture: Fostering Rural Tourism, Well-Being, and Sustainability - Miroslav Knežević; Aleksandra Vujko; Dušan Borovčanin (Agriculture)
This study explores the role of community-centered farm-based hospitality in promoting sustainable rural development, with a focus on South Tyrol, Italy. A survey of 461 local residents assessed perceptions of agritourism’s impact on agricultural heritage, environmental sustainability, and community well-being. Factor analysis identified two main constructs—Agroheritage Sustainability and Empowered Eco-Tourism—which together capture the multifaceted benefits of agritourism. Agroheritage Sustainability reflects the preservation of traditional farming practices, cultural landscapes, and intergenerational knowledge, emphasizing the role of tourism in maintaining cultural identity and preventing land abandonment. Empowered Eco-Tourism highlights the socio-economic benefits of sustainable tourism, including community empowerment, environmental stewardship, and the creation of new economic opportunities. The study’s findings indicate that local residents view agritourism as a holistic approach that supports rural livelihoods while preserving cultural heritage and promoting ecological resilience. The analysis further supports the potential of farm-based hospitality as a model for sustainable rural development, aligning closely with EU policies and global best practices. The Roter Hahn initiative in South Tyrol serves as a practical example of this approach, demonstrating the value of certification programs in enhancing transparency, quality, and sustainability. These insights provide valuable guidance for policymakers and tourism developers seeking to promote sustainable rural tourism globally. The contribution of this research lies in its empirical validation of a dual-construct model that links community engagement with agroecological and cultural sustainability, offering a transferable framework for evaluating agritourism as a lever for sustainable rural development in diverse regional contexts.